Pengembangan media penyuluhan Manajemen Terpadu Balita Sakit (MTBS) bagi tenaga kesehatan di Pusat Kesehatan Masyarakat (Puskesmas) - Heni Purwaningsih; Fiki Wijayanti; Trimawati Trimawati (Health Sciences and Pharmacy Journal, 2020)
Decreasing child mortality is still a target of health development in Indonesia. One effort is to increase knowledge through health promotion. Giving promotion is effective and optimal by using of media such as flash cards. Flash card is a picture card media with information on each picture. The purpose of this study is to measure the effectiveness of flashcard information media on the knowledge of health workers in primary health center. This type of research was Quasi Experimental with pre-post test in one group (One-Group Pre-test-posttest Design). The population of this research was 28 health workers in Ungaran Health Center and Lerep Health Center. Data collection tool in the form of a questionnaire and media information in the form of a flashcard, with the sampling technique was total sampling. Statistical test used Wilcoxon test.Conclusion was The results showed there were significant differences in the knowledge of health workers after counseling using a flashcard with a p value of 0,001 < α (0,05). The average value of knowledge before the intervention was 38,61 and thereafter increased become 42,79. The conclusion was health education using flashcard information media is effective to increase the knowledge of health workers about IMCI in primary health center